Sistema de Gestión de Auditorías para el Centro de Soporte UCI - Almaguer-Perez, Dairis (Revista Científica, 2016)
This article is part of an investigation for the realization of a system to audit procedures performed in the support center of the University of Information Sciences (UCI). The goal of implementing this system is to increase the provision of Information Technology (IT) in the center. To carry out the implementation of the system were analyzed management systems audit of IT services exist today as a result of a deep study of art in the national and international level, the tools and technologies used are described in the solution developed (methodology, patterns, software, programming languages, etc.) that allow efficient implementation in a short time the proposed system. The prior written positively reflected in better customer satisfaction and therefore greater acceptance of services provided by the entity.